Erratum: Strike and Fielding Games pada Keterampilan Gerak dasar - Vicki Ahmad Karisman; Gita Febria Friskawati (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v5i1.710 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.